Zirconyl (IV) Nitrate as Efficient and Reusable Solid Lewis Acid Catalyst for the Synthesis of Benzimidazole Derivatives - Pratapsinha B. Gorepatil; Yogesh D. Mane; Vilas S. Ingle (Journal of Chemistry)
The present paper introduces a simple and efficient method for the synthesis of substituted benzimidazoles by heterocyclization of different o-phenylenediamines and substituted aromatic carboxylic acid/aldehyde in the presence of zirconyl nitrate as catalyst in ethanol under reflux, which produced excellent yield of corresponding benzimidazoles in a short reaction time with reusability of catalyst.